FROM THE HISTORY OF SCIENTIFIC AND INNOVATIVE ACTIVITY OF GERMANY IN THE 21ST CENTURY - Umarov Sardor Yakubovich (Uzbekistan Open Conference, 2025)
Innovation has become another important driver of economic restructuring in Germany. New products and new processes offer the opportunity to increase sales and profits and create new jobs. The article analyzes the scientific and innovation processes that took place in Germany after reunification and the issues that were addressed in this process. At the same time, the author thoroughly studied the negative and positive aspects of innovation in the 21st century. Научно-технические и социокультурные проблемы современного общества.
Keywords: Scientific development; regional planning; technological regions; innovative efficiency; investment